1965
DOI: 10.1136/hrt.27.5.684
|View full text |Cite
|
Sign up to set email alerts
|

Renal response to paroxysmal tachycardia.

Abstract: The pattern of water and solute excretion during paroxysmal tachycardia has been studied by Borst and his colleagues (Blomhert, 1951;Borst, 1941;Borst et al., 1960). They showed that with the onset of paroxysm there was a striking water diuresis which continued for the duration of the paroxysm and then stopped. An increase in sodium chloride excretion was also recorded at some time in the attack. Creatinine excretion was constant. A case studied by Wood (1963) developed a diuresis during a paroxysm which was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In addition to SVT, polyuric response has also been noted after the episodes of atrial fibrillation, atrial flutter, and ventricular tachycardia. The characteristics of the diuresis during SVT include an increase in urine flow and volume, free water clearance, and sodium excretion and a decrease in urine osmolality [16][17][18][19].…”
Section: Diagnostic Challenges In Supraventricular Tachycardiamentioning
confidence: 99%
“…In addition to SVT, polyuric response has also been noted after the episodes of atrial fibrillation, atrial flutter, and ventricular tachycardia. The characteristics of the diuresis during SVT include an increase in urine flow and volume, free water clearance, and sodium excretion and a decrease in urine osmolality [16][17][18][19].…”
Section: Diagnostic Challenges In Supraventricular Tachycardiamentioning
confidence: 99%
“…paroxysmal tachycardia volume receptors baroreceptors vascpressin natriuresis atrial pacing complete heart block • A diuresis frequently accompanies attacks of paroxysmal tachycardia (1)(2)(3)(4)(5)(6). Although the etiology of the diuresis is unknown, several investigators have suggested that the increase in urine flow is elicited reflexly from atrial receptors (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Several workers (9)(10)(11) have shown that a water diuresis results in man during atrial arrhythmias such as paroxysmal atrial tachycardia, atrial flutter, and atrial fibrillation. During these arrhythmic episodes, atrial receptor discharge is increased due to a concomitant rise in mean atrial pressure.…”
mentioning
confidence: 99%